Efficient Reactive Power Compensation Algorithm for Distribution Network - J. Jerome (Universitas Gadjah Mada, 2003)
The use of automation and energy efficient equipment with electronic control would greatly improve industrial production. These new devices are more sensitive to supply voltage deviation and the characteristics of the power system that was previously ignored are now very important. Hence the benefits of distribution automation have been widely acknowledged in recent years. This paper proposes an efficient load flow solution technique extended to find optimum location for reactive power compensation and network reconfiguration for planning and day-to-day operation of distribution networks. This is required as a part of the distribution automation system (DAS) for taking various control and operation decisions. The method exploits the radial nature of the network and uses forward and backward propagation technique to calculate branch currents and node voltages. The proposed method has been tested to analyze several practical distribution networks of various voltage levels and also having high R/X ratio.